A comparison of HIV/AIDS-related stigma in four countries: Negative attitudes and perceived acts of discrimination towards people living with HIV/AIDS - Becky L. Genberg (2018)
HIV/AIDS-related stigma and discrimination have a substantial impact on people living with HIV/AIDS (PLHA). The objectives of this study were: (1) to determine the associations of two constructs of HIV/AIDS-related stigma and discrimination (negative attitudes towards PLHA and perceived acts of discrimination towards PLHA) with previous history of HIV testing, knowledge of antiretroviral therapies (ARVs) and communication regarding HIV/AIDS and (2) to compare these two constructs across the five research sites with respect to differing levels of HIV prevalence and ARV coverage, using data presented from the baseline survey of U.S. National Institute of Mental Health (NIMH) Project Accept, a four-country HIV prevention trial in Sub-Saharan Africa (Tanzania, Zimbabwe and South Africa) and northern Thailand. A household probability sample of 14,203 participants completed a survey including a scale measuring HIV/AIDS-related stigma and discrimination. Logistic regression models determined the associations between negative attitudes and perceived discrimination with individual history of HIV testing, knowledge of ARVs and communication regarding HIV/AIDS. Spearman's correlation coefficients determined the relationships between negative attitudes and perceived discrimination and HIV prevalence and ARV coverage at the site-level. Negative attitudes were related to never having tested for HIV, lacking knowledge of ARVs, and never having discussed HIV/AIDS. More negative attitudes were found in sites with the lowest HIV prevalence (i.e., Tanzania and Thailand) and more perceived discrimination against PLHA was found in sites with the lowest ARV coverage (i.e., Tanzania and Zimbabwe). Programs that promote widespread HIV testing and discussion of HIV/AIDS, as well as education regarding and universal access to ARVs, may reduce HIV/AIDS-related stigma and discrimination. © 2009.